UPAYA GURU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA TUNAGRAHITA DENGAN MENGOPTIMALKAN PENGGUNAAN MEDIA YANG ADA DI LINGKUNGAN SEKOLAH DI SEKOLAH DASAR LUAR BIASA SARONGGI KABUPATEN SUMENEP - Iwan Kuswandi; Mafruhah Mafruhah (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2018)
Media can improve the quality of learning process. At the time of teaching, teachers must know the preferences and interest of student to the media in accordance with the psychology of his students, especially mentally disabled students. This study aims to inventory the exist- ing learning media in SDLB Saronggi Sumenep, and to know about the teacher’s efforts in improving the learning motivation of mentally disabled students by optimizing the use of ex- isting environment media in SDLB Saronggi, Sumenep. This research uses mixed methods, with research design using sequential explanatory. In SDLB Saronggi, learning media other than class, also has multipurpose room, video for learning, LCD projector, a shady schoolyard, shelves and creativity boards, fruits, props for learning, a set of traditional musical instru- ments Madura. The existence of various media can improve the motivation of learn mentally disabled students. Proven results using calculations Wilcoxon Scien R test earned value Zcount amount (-3,162), because of the score (-3,162) is a absolute score, greater than Ztable = 1,96 or (-3,162 > 1,96) then H0 rejected and Ha be accepted. It can be concluded that the environmental media around the school can improve motivation of learn mentally disabled students SDLB Saronggi.